The constitution is the basic structure of Kyrgyzstan authority state (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article reveals the main problems of modern constitutional development in the conditions of global social transformation; the main features of an authoritative state and the place of the Constitution in it are analyzed; the ways of further constitutional development of Kyrgyzstan in difficult modern conditions are revealed. The thesis is put forward that for the near future, the renewal of the legal mechanisms for implementing the tasks of the Constitution, the scientific determination of the criteria for the constitu
Keywords: constitution, constitutional mechanisms, constitutional development, law, legal regulation, legal nihilism, authoritative state